Post-calcination, a novel method to synthesize cobalt oxide-based thermoelectric materials - Kang, Min-Gyu; Cho, Kwang-Hwan; Kim, Jin-Sang; Nahm, Sahn; Yoon, Seok-Jin; Kang, Chong-Yun (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Cobalt oxide-based Ca3Co4O9 ceramics are known for their good thermoelectric (TE) performance and chemical stability at high temperatures (<900 degrees C); however, the crystalline phase of these ceramics is unstable beyond 926 degrees C due to thermal decomposition. This low limit (926 degrees C) on the sintering temperature produces a very low-density material with poor TE properties. Here, a novel method (post-calcination) to synthesize high-density and single-phase Ca3Co4O9 ceramics is investigated by high-temperature X-ray diffraction analysis. The post-calcination method, which includes cooling and reheating of the phase decomposed Ca3Co4O9 ceramics, synthesizes high-density (relative density = 92%) and single-phase Ca3Co4O9 ceramics via a solid-state reaction at a high sintering temperature of 1200 degrees C, and improved TE properties (power factor = 0.245 mW K-2 in 1 at 800 degrees C) are observed. The post-calcination method is expected to be applicable to Ca3Co4O9 and other materials that are difficult to obtain in high-density form due to thermal decomposition. Furthermore, this technique improves the sinterability and production efficiency without using complicated processes. (C) 2014 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: MISFIT-LAYERED COBALTITE; CA3CO4O9; ENHANCEMENT; THERMODYNAMICS; THERMOPOWER; PERFORMANCE; FABRICATION; TRANSITION; CO3O4; POWER